LIVE EXPERIENCE OF ACADEMIC CULTURE ADJUSTMENT IN INTERNATIONAL CREDIT TRANSFER PROGRAM: A PHENOMENOLOGICAL STUDY - Wahyudi, Ricky; Maulina , Maulina; Muflihun, Muflihun (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This phenomenological study investigates the Muhammadiyah University of Kendari students' lived experiences who underwent academic cultural adjustments during an international credit transfer (ICT) program to the Nueva Ecija University of Science and Technology (NEUST) in the Philippines. This research applied in-depth interviews to understand the unique challenges, coping strategies, and transformation impact by the purposively selected students. These findings provide valuable insight into the feelings gained during the study and the transformative nature of the academic cultural adjustment experience and highlight factors that facilitate or hinder successful adjustment in the specific context of Muhammadiyah University of Kendari students to NEUST. These findings can inform both institutions regarding the specific needs and challenges students face during academic cultural adjustment and guide the development of targeted interventions, support systems, and resources to enhance the academic success and well-being of students involved in the ICT programs